2014
DOI: 10.1016/j.rboe.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage lesions and ankle osteoarthrosis: review of the literature and treatment algorithm

Abstract: The main etiology of ankle osteoarthrosis is post-traumatic and its prevalence is highest among young individuals. Thus, this disease has a great socioeconomic impact and gives rise to significant losses of patients’ quality of life. The objective of its treatment is to eliminate pain and keep patients active. Therefore, the treatment should be staged according to the degree of degenerative evolution, etiology, joint location, systemic condition, bone quality, lower-limb alignment, ligament stability and age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
0
11
0
2
Order By: Relevance
“…Despite the high prevalence of ligamentous ankle injuries, PTOA does not always develop, even in patients with known chondral lesions. In fact only 16% of ankle arthritis cases are due to ligamentous injuries . Despite having much higher contact pressures than both the hip and knee, the articular cartilage of the ankle is actually thinner, stiffer, contains the highest glycosaminoglycan (GAG) content, is the most metabolically active, and has the highest turnover of the important cartilaginous protein aggrecan compared to both the hip and knee .…”
Section: Common Injuries Associated With Post‐traumatic Osteoarthritismentioning
confidence: 99%
“…Despite the high prevalence of ligamentous ankle injuries, PTOA does not always develop, even in patients with known chondral lesions. In fact only 16% of ankle arthritis cases are due to ligamentous injuries . Despite having much higher contact pressures than both the hip and knee, the articular cartilage of the ankle is actually thinner, stiffer, contains the highest glycosaminoglycan (GAG) content, is the most metabolically active, and has the highest turnover of the important cartilaginous protein aggrecan compared to both the hip and knee .…”
Section: Common Injuries Associated With Post‐traumatic Osteoarthritismentioning
confidence: 99%
“…However, there are many indications that open reduction and internal fixation of deviated fractures greatly reduce the risk of premature closures when compared with conservative therapy 11, 12, 13. Many studies have shown better long-term outcomes in patients treated with anatomical reduction 14, 15, 16…”
Section: Malleolar Fracturesmentioning
confidence: 99%
“…The experience with deviated cuboid fractures in the pediatric population is limited to case reports 10, 14, 15, 21, 24, 27, 29, 42. These injuries often result in subluxation or Chopart joint dislocation, as they are usually associated with other foot fractures 4, 12, 14, 20, 27…”
Section: Chopart and Lisfranc Fracture-dislocationsmentioning
confidence: 99%
“…These causes lead to an imbalance between the synthesis and degradation of articular cartilage and the subchondral bone (Camanho et al, 2011). This disease causes functional changes in 15% of the worldwide adult population, affecting subjects mainly subjects over 60 years old (Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%